Electron correlation driven non-adiabatic relaxation in molecules excited by an ultrashort extreme ultraviolet pulse - Marciniak, Alexandre; Despré, Victor; Kuleff, Alexander I. (Nature Communications, 2019)
The many-body quantum nature of molecules determines their static and dynamic properties, but remains the main obstacle in their accurate description. Here, the authors employ ultrafast spectroscopic methods to explore the dynamics of highly excited organic molecules, revealing many-body effects and hints of coherent vibronic dynamics which persist despite their molecular complexity.
Gesehen am 06.03.2019